Blind recognition of real orthogonal STBC based on independent component analysis - Zhi-jin ZHAO; Lin CHEN; Hai-quan WANG; Lei SHEN (Tongxin xuebao)
A method for blind recognition of orthogonal space-time block coding (OSTBC) based on independent component analysis (ICA) was proposed.Firstly,the model of received signal was given.And then independent component analysis technology was used to separate the virtual channel matrix which contains coding matrix information.Using the characteristics of coding matrix,it was proved that the correlation matrix of the virtual channel matrix in OSTBC communication systems was diagonal matrix.Finally,two characteristic parameters were proposed: sparsity and variance,which could recognize OSTBC.Simulation results demonstrated that the proposed method is able to identify OSTBC while achieves good performance.